AN ANALYSIS OF STUDENTS’ WAYS IN ANSWERING MULTIPLE CHOICE QUESTION ON READING TOEFL TEST - Sinta Agustika (Teaching English and Language Learning English Journal, 2021)
The objectives of this research are to find the ways by the students in answering multiple choice question on reading TOEFL test and to find out the dominant way used by the students in answering multiple choice question on reading TOEFL test. The design of this research was a descriptive qualitative research,because in this research, the researcher describes the students’ ways in answering  multiple choice question on reading TOEFL test.Subject of the research is the whole students with 50 total students. The Instrument of this research was questionnaire.Questionnaire is a list of question that describe of something.The questionnaire is designed based on Cohen and Upton (2006) theory. The are two main ways in answering multiple choice questions : Test Management Strategies Coding Rubic (T) and Test-Wisenes Strategies Coding Rubic (TW).Test Management Strategies Coding Rubic (T) consist of 28 Strategies and Test Wiseness Strategies Coding Rubic (TW) consist of 3 strategies.So,the total items of questionnaire is 31 items.The researcher finding showed that the dominant way used by the students in answering multiple choice question on reading TOEFL test was Test-wiseness Strategies Coding Rubic (TW).Key words: Student’s ways,Answering Question,Reading TOEFL Test